Numerical and Experimental Investigation on the Effect of Billet Preforming in the Flange Forming - M.N, Abdullah; ., . (International Journal of Engineering and Technology, 2018)
Finite element method and experiments have been used to study a cold forming method for fabrication of a flange using the effect of billet preforming. Three dimensional finite element methods carried out to obtain the forming load, die filling, material flow, effective stress, effective strain with DEFORM-3D software, and a series of experimental works has been performed using lead metal with four types of billet preforming in the first stage. Pressing process has been done using computerized hydraulic press machine with 100 tons. The forming sequence is carried out in two stages. In the first stage, the cylindrical billet is preformed by upsetting and in the second stage forming it in a die. Results indicate that the process of formation is influenced by preforming of billet with fixed volume in the final stage of pressing, improve the mechanical properties of the metal and thus facilitates the final deformation process with less stress and better flow of the metal inside the die. Simulation results show that the effective stress, maximum principal stress, effective strain, velocity and damage are maximum at locations where flange open out and rib growth begins across the geometrical interlocking between the two halves of die-set and the component surface.